Screening potential mitochondria-targeting compounds from traditional Chinese medicines using a mitochondria-based centrifugal ultrafiltration/liquid chromatography/mass spectrometry method - Xing-Xin Yang; Yu-Zhen Zhou; Feng Xu; Jie Yu; Gegentana; Ming-Ying Shang; Xuan Wang; Shao-Qing Cai (Elsevier, 2018)
Mitochondria regulate numerous crucial cell processes, including energy production, apoptotic cell death, oxidative stress, calcium homeostasis and lipid metabolism. Here, we applied an efficient mitochondria-based centrifugal ultrafiltration/liquid chromatography/mass spectrometry (LC/MS) method, also known as screening method for mitochondria-targeted bioactive constituents (SM-MBC). This method allowed searching natural mitochondria-targeting compounds from traditional Chinese medicines (TCMs), including Puerariae Radix (PR) and Chuanxiong Radix (CR). A total of 23 active compounds were successfully discovered from the two TCMs extracts. Among these 23 hit compounds, 17 were identified by LC/MS, 12 of which were novel mitochondria-targeting compounds. Among these, 6 active compounds were analyzed in vitro for pharmacological tests and found able to affect mitochondrial functions. We also investigated the effects of the hit compounds on HepG2 cell proliferation and on loss of cardiomyocyte viability induced by hypoxia/reoxygenation injury. The results obtained are useful for in-depth understanding of mechanisms underlying TCMs therapeutic effects at mitochondria level and for developing novel potential drugs using TCMs as lead compounds. Finally, we showed that SM-MBC was an efficient protocol for the rapid screening of mitochondria-targeting constituents from complex samples such as PR and CR extracts. Keywords: Mitochondria, Bioactive constituents, Traditional Chinese medicines, Centrifugal ultrafiltration, Liquid chromatography/mass spectrometry